A reader in medical anthropology : theoretical trajectories, emergent realities - Good, Byron J. (Blackwell anthologies in social and cultural anthropology, 2010)
Presents a key collection of both classic and new agenda-setting articles in this central area of anthropology ? Provides analytic and historical contextual introductions by leading figures in medical anthropology, medical sociology, science studies, social theory and general anthropology